(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The materials presented in the article complete the research of the domains (subscales) of the psychophysical state of higher education students (1st year) according to the Multidimensional Assessment of Interoceptive Awareness scale. This questionnaire with eight subscales has a Ukrainian-language version, created and tested by the Ukrainian scientist Y. Voloshchenko, and is called MAIA-2ukr (2022). Modern specialists are unanimous that a person needs to understand and be aware of his physical condition to reduce stress and choose an adequate load on the body. Future physical education teachers, trainers, instructors, and pedagogues should also possess self-control skills. Somatic movements help develop an awareness of the processes in the body and identify places in tension or spasm. With the help of the questionnaire, the respondents redirected their attention to their inner feelings, trying to be aware of what was happening. A crucial methodical aspect of somatic movement classes is a story after practice about your experience in this class. Students focus their attention on self-reporting, realizing what happened to the body. Sometimes, people feel they have become "heavier" or "lighter" or cannot explain the sensation difference. Systematic classes gradually give a person a particular experience, and his body feels more individual and profound. It is interesting that somatic movement classes, even for the same group of muscles, are perceived differently because a person comes to a class already in a different state than he was in the previous class. A person’s interoceptive awareness also affects the development of coordination abilities because every lesson has elements that are perceived as new. To characterize the current state of students, we conducted a survey. Fifty people participated in the study: boys and girls aged 17-19, first-year students of the Faculty of Health, Physical Education and Sports of the Borys Grinchenko Kyiv Metropolitan University. In the previous articles, data was presented on the following subscales: "Noticing," "Not Distracting," "Not Worrying," "Attention Regulation," "Emotional Awareness," and "Self-Regulation." The next subscale (domain 7) is called "Body Listening," and the extreme subscale (domain 8), "Trusting," completes the analysis of our survey according to the MAIA-2ukr (2022) version.